Adsorption of Some Metal Chelates on Polystyrene Divinyl Benzene Copolymers - Soylak, Mustafa (Asian Journal of Chemistry, 2012)
In the present work, adsorption of metal chelates (8-hydroxyquinoline and 1-nitroso-2-naphthol chelates) on the surface of polystyrene divinyl benzene copolymers (amberlite XAD-4 and diaion HP-20) resin were investigated by using flame atomic absorption spectrometry (FAAS) and scanning electron microscope (SEM). The optimal conditions for the quantitative adsorption and recovery of the metal ions on diaion HP-20 and amberlite XAD-4 were discussed.